Optimization of Enzymatic Protein Hydrolysate from Mung Bean (Vigna radiata L.), and Its Functional Properties - Kanokwan Promjeen; Suphat Phongthai; Kanjana Singh; Worrapob Chaisan; Peeraporn Pakakaew; Somdet Srichairatanakool; Rajnibhas Sukeaw Samakradhamrongthai; Niramon Utama-ang (Foods)
Mung bean is a rich protein source, but its native form has limited solubility and functionality for food applications. As a promising agro-based crop, mung bean offers a sustainable alternative to traditional protein sources, especially in regions with limited access to resources. This study optimized mung bean protein hydrolysate (MBPH) production using response surface methodology (RSM), investigating the effects of alcalase concentration (2–7%) and hydrolysis time (2–7 h) on its physicochemical and functional properties. The results showed that an alcalase concentration of 5.88% and a hydrolysis duration of 3.56 h were the optimal conditions, resulting in a degree of hydrolysis of approximately 33.09%. Under these conditions, MBPH contained 79.33 ± 0.62% protein and a molecular weight distribution of 45.57% and 47.29% at 1.1–10 kDa and <10 kDa, respectively. Additionally, MBPH exhibited strong antioxidant activity, improved foam capacity, and enhanced solubility, making it a valuable ingredient for sustainable food production and promoting equitable access to nutritious functional ingredients.